Corneal oedema during open‐eye fenestrated scleral lens wear. (17th May 2022) - Fisher, Damien; Collins, Michael J; Vincent, Stephen J
Abstract: Introduction: Studies examining the effect of fenestrating soft and corneal rigid contact lenses upon corneal oedema have yielded conflicting results. Although often utilised in clinical practice, no studies have quantified the effect of fenestrating a scleral contact lens upon corneal oedema. Therefore, the aim of this experiment was to examine the effect of incorporating a single peripheral fenestration on central corneal oedema during short‐term open‐eye scleral lens wear, while controlling for potential confounding variables. Methods: Nine participants (mean age 30 years) with normal corneas wore a fenestrated (1 × 0.3 mm limbal fenestration) and non‐fenestrated scleral lens (both lenses manufactured using a material Dk of 141 × 10 −11  cm 3 O2 (cm)/[(sec.)(cm 2 )(mmHg)]) under open‐eye conditions on separate days. Scleral lens thickness profiles were measured using a high‐resolution optical coherence tomographer (OCT). Epithelial, stromal and total central corneal oedema were also measured using the OCT immediately after lens application and following 90 min of wear, prior to lens removal. Results: After adjusting for differences in initial central fluid reservoir thickness and scleral lens thickness between the two lens conditions, the mean (standard error) total corrected central corneal oedema was 0.50 (0.36)% for the fenestrated lens and 0.62 (0.16)% for the non‐fenestrated lens. This small difference was not statistically significant (t8  = 2.31, p  = 0.81) and represents a 19% relative reduction in central corneal oedema. Similarly, epithelial (t8  = 2.31, p  = 0.82) and stromal (t8  = 2.31, p  = 0.92) corneal oedema were not significantly different following the fenestrated and non‐fenestrated wearing conditions. Conclusion: Central corneal oedema in healthy corneas was comparable between fenestrated and non‐fenestrated high Dk scleral lenses under short‐term open‐eye conditions when controlling for lens oxygen transmissibility and initial central fluid reservoir thickness.